(untitled) (Research, Society and Development, 2022)
Objective: The present study aims to compare the incidence of dengue from the first recorded case to the present day. Method: This is an ecological study with a quantitative approach. The Informatics Department of the Unified Health System (SUS) - DATASUS was used to obtain data from the Notifiable Diseases Information System (SINAN) for the item "Epidemiological and Morbidity". Annual notifications of dengue cases in Brazil from 1975 to 2022 were included. Exclusion criteria include data on states that are not part of the region or year analyzed. Result and discussion: Dengue is a serious public health problem in the country since its first appearance and its incidence has been growing over time, especially after 2007, this fact is due to increasing urbanization. Conclusion: According to the data collection, there was an outbreak of dengue cases in Brazil in 2007 and since then dengue cases have never been below 200,000 cases in the country, becoming an alert in the health area because it is a disease that causes high mortality.